Leveraging the competency of condition monitoring system for achieving excellence in operations management - Varun Tripathi; Alok Bhadauria (Discover Sustainability)
Abstract The condition monitoring system is an integral section of operations management on the shop floor. Condition monitoring means prior information of failure before machinery malfunctions and shuts down. If the industry personnel fail to control the machinery performances on the shop floor, then they face severe circumstances in operations management. Operations management teams use manual and automated evaluation equipment for taking suspicious machinery behaviors. However, the current operational scenario needs the advanced condition monitoring system for tackling the operations management issues in terms of machinery performance because machinery failure results in drastic deterioration in operational and financial outcomes. The current dynamic operations management scenario reports that machinery performance directly affects the outcomes on the shop floor. The present study developed a framework for a real-time condition monitoring system in operations management on the shop floor. The developed framework is implemented in a real-life case of the electric vehicle manufacturing industry. The study observed fifteen days of the production logistics system and evaluated multiple operating conditions. The developed system considers different factors and parameters, including machinery failure, vibration level, faulty products, noise status, product quality, idle time, scheduling, and workplace hygiene. The operation planning teams helped in investigating the developed framework by implementing it in the next six days' production logistics conditions. The result showed that the developed framework for real-time condition monitoring system provides operations management excellence by improving the production logistics system performances. The investigation showed a reduction in idle time, machinery failure, and faulty manufacturing by 84.33%, 40.74%, and 28.43%, respectively, and improved workforce reliability by 87.5%. The current approach can help shop floor managers in condition monitoring systems for operational and financial sustainability.